The Addition of Propylene Glycol Alginate to a Fluoride Solution to Control Enamel Wear: An in situ Study - Sakae, Letícia Oba; Niemeyer, Samira Helena; Bezerra, Sávio José Cardoso; Borges, Alessandra Buhler [UNESP]; Turssi, Cecilia Pedroso; Scaramucci, Taís (Karger Publishers, 2020)
The aim of this study was to evaluate the protective effect of propylene glycol alginate (PGA) associated with sodium fluoride (NaF) against enamel erosion and erosion-abrasion. A 4-phase, split-mouth, double-blind, crossover in situ trial was conducted with the following solutions: F + PGA (225 ppm Fsup-/sup + 0.1% PGA), F (225 ppm Fsup-/sup), F + Sn (225 ppm Fsup-/sup + SnClsub2/sub, 800 ppm Snsup2+/sup), and negative control (distilled water). In each phase, 12 subjects wore removable mandibular appliances containing 4 enamel specimens, which were submitted either to erosion or to erosion-abrasion challenges for 5 days. Acquired salivary pellicle was formed in situ for 2 h. Erosion-abrasion consisted of acid challenge (1% citric acid solution, pH 2.3, 5 min, 4×/day), exposure to saliva in situ (2 h, 4×/day), brushing (5 s, total 2 min exposure to the slurry), and treatment with the solutions (2 min, 2×/day). For erosion, the same procedures were performed, without brushing. At the end, surface loss (SL; in μm) was evaluated by means of optical profilometry. KOH-soluble fluoride was quantified for erosion-only groups using extra specimens. For both challenges, the SL values found for F + PGA did not differ significantly from those of F and the negative control, and the SL value shown for F + Sn was significantly the lowest. Erosion-abrasion promoted significantly higher SL values than erosion. KOH-soluble fluoride analysis showed that F + Sn had a higher fluoride concentration in comparison with the negative control and F, while F + PGA did not differ from any of the other groups. In conclusion, PGA was not able to improve the protective effect of NaF against erosive enamel wear.
Keywords: Fluoride; In situ study; Polymer; Profilometry; Propylene glycol alginate solution; Tooth wear